DIVERSI TINDAK PIDANA NARKOTIKA DALAM SISTEM PERADILAN PIDANA ANAK - I Made Wiharsa (University of Udayana, 2017)
Diversion of narcotic crime in the criminal justice system for the children. Children in conflict with the law, especially in narcotic cases not specifically regulated in Law Number 35 of 2009 on the Narcotics. During this time the children in conflict with the law that is drafted in the Law Number 11 of 2012 on the Criminal Justice System for The Children. Criminal punishment against with a certain person started because that person has committed a crime. Children in the case of a criminal act of narcotics criminal sanctions will have a negative impact on a child's future. Referring to the criminal justice system for the children are known to attempt a diversion to divert the child's completion of the criminal case of the trial into a non-judicial process. This research with the normative methods research type, which aims to determine the impact of the imposition of criminal sanctions and diversion efforts for children in narcotic crime. Diversi tindak pidana narkotika dalam sistem peradilan pidana anak. Anak yang berkonflik dengan hukum khususnya dalam tindak pidana narkotika belum diatur secara khusus dalam Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika. Selama ini terhadap anak yang berkonflik dengan hukum mengacu pada Undang-Undang Nomor. 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak. Penjatuhan pidana terhadap seseorang bermula karena seseorang tersebut telah melakukan suatu tindak pidana. Anak dalam hal melakukan tindak pidana narkotika yang dijatuhi sanksi pidana akan berdampak buruk pada masa depan anak. Mengacu pada sistem peradilan pidana anak yang dikenal upaya diversi untuk mengalihkan penyelesaian perkara tindak pidana anak dari proses peradilan ke proses non peradilan. Penelitian ini menggunakan metoda penelitian hukum normatif, yang bertujuan untuk dapat mengetahui dampak penjatuhan sanksi pidana dan upaya diversi bagi anak dalam tindak pidana narkotika.